2013
DOI: 10.1021/om400057e
|View full text |Cite
|
Sign up to set email alerts
|

Half-Sandwich Ruthenium(II) Complexes of Click Generated 1,2,3-Triazole Based Organosulfur/-selenium Ligands: Structural and Donor Site Dependent Catalytic Oxidation and Transfer Hydrogenation Aspects

Abstract: 1-Benzyl-4-((phenylthio)-/(phenylseleno)methyl)-1H-1,2,3-triazole (L1/L2) and 4-phenyl-1-((phenylthio)-/(phenylseleno)methyl)-1H-1,2,3-triazole (L3/L4) synthesized using the click reaction have been reacted for the first time with [{(η6-C6H6)RuCl(μ-Cl)}2] and NH4PF6 to design the half-sandwich complexes [(η6-benzene)RuLCl]PF6 (1–4 for L = L1–L4), which have been characterized by single-crystal X-ray diffraction and explored for the catalytic oxidation of alcohols with N-methylmorpholine N-oxide (NMO) and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
152
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(156 citation statements)
references
References 128 publications
4
152
0
Order By: Relevance
“…In conclusion, the electronic stability of complexes involving N(1) in coordination was greater than in those involving N(2) and so their reactivity is less. 37,56,126,208 It should be noted that the crystallographical structural data for complexes 46, 47, and 48 were in good agreement with the calculated values.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…In conclusion, the electronic stability of complexes involving N(1) in coordination was greater than in those involving N(2) and so their reactivity is less. 37,56,126,208 It should be noted that the crystallographical structural data for complexes 46, 47, and 48 were in good agreement with the calculated values.…”
supporting
confidence: 76%
“…57 It was shown that in the following Pd complexes, the calculated electron densities at Se, Pd, and N(3) of the triazole ring were higher in complex 16 than in complex 15, mainly due to the strong metal-ligand interaction in complex 16 and its subsequent higher stability and lower reactivity relative to complex 15. 37,56,126 Moreover, in these complexes, there was a good agreement between the experimentally observed and calculated bond distances and angles. However, some of calculated Pd-M bond distances (M ¼ S/Se) deviated from the corresponding observed ones.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Development of sustainable protocols for the synthesis of 1,2,3‐triazole scaffolds have emerged one of the thrust area of research for organic chemist due to their exclusive pharmaceutical, agrochemical, medicinal and many other applications . Several strategies have been reported for the synthesis of 1,2,3‐triazoles and Huisgen's dipolar cycloaddition of organic azides and alkynes is the most straightforward route .…”
Section: Figurementioning
confidence: 99%
“…Singh and co‐workers prepared a series of ruthenium catalysts ( 44–47 ), which they used for the oxidation of primary and secondary alcohols (in the presence of N ‐methylmorpholine N ‐oxide) and for the hydrogenation of ketones (Scheme ) . The catalysts, in which the N2 atom is bound to ruthenium ( 46 , 47 ), were shown to be more efficient than those involving N3–metal coordination.…”
Section: Triazoles As Ligands In Catalytic Reactionsmentioning
confidence: 99%